2016
DOI: 10.1080/13218719.2016.1142934
|View full text |Cite
|
Sign up to set email alerts
|

A Lie and a Mistress: On Increasing the Believability of Your Alibi

Abstract: The present study was designed to assess whether or not the presentation method and the salaciousness of an alibi affect its evaluation. Community participants (n D 150) were asked to evaluate the salacious or non-salacious alibi of a crime suspect. The alibi was either presented immediately after arrest by the suspect or was changed after the initial alibi turned out to be incorrect. The incorrect alibi was due to either a misrecollection or a deliberate lie. We found that when the initial alibi was changed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…A selection bias could be a second limitation of the present study because at first, the friends and family of the first author were asked to fill out and forward the questionnaire. Nieuwkamp et al () used a similar methodology where a second group of participants (i.e., a sample of community members who were recruited in a dance school) was added to control for a possible selection bias. No difference was observed between both groups of participants for their demographics and their answers on the dependent variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A selection bias could be a second limitation of the present study because at first, the friends and family of the first author were asked to fill out and forward the questionnaire. Nieuwkamp et al () used a similar methodology where a second group of participants (i.e., a sample of community members who were recruited in a dance school) was added to control for a possible selection bias. No difference was observed between both groups of participants for their demographics and their answers on the dependent variables.…”
Section: Discussionmentioning
confidence: 99%
“…At first, friends, colleagues, and family from the first author were sent an e‐mail with the link. They were in turn asked to send their colleagues and friends the link to the questionnaire because we aimed at a large sample of participants, a similar method as used by Nieuwkamp et al (). In that study, the authors selected two groups of community members.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, further demonstrating people's intolerance for memory errors, Nieuwkamp, Horselenberg and Van Koppen () found that people were more tolerant of a person changing their alibi because they lied the first time – to cover up the fact they were doing something salacious – than merely because they made a mistake.…”
Section: Alibi Evaluation Phasementioning
confidence: 99%
“…Strange, Dysart, & Loftus, 2014). Lastly, a suspect may also lie about an alibi to conceal his or her involvement in another, but shameful situation (Nieuwkamp, Horselenberg, & Van Koppen, 2016). The assumption that non-offenders are able to present strong supportive evidence for their alibis has proven to be incorrect (Culhane, Hosch, & Kehn, 2008;Culhane et al, 2013;Olson & Charman, 2012).…”
Section: Alibi Researchmentioning
confidence: 99%